KEKERASAAN DALAM RUMAH TANGGA TERHADAP PEREMPUAN DI KRUENG ALEM DARUL MAKMUR KABUPATEN NAGAN RAYA - Mella Sartika; Rahma Husna Yana (Jurnal Society : Pengamat Perubahan Sosial, 2021)
This study was conducted to determine the factors and impacts that caused conflict in Krueng Alem Village, Darul Makmur District, Nagan Raya Regency which resulted in domestic violence, the theory used was Randall Collins' conflict theory. The method used in this study is a qualitative descriptive method. The results of this study which become a factor in domestic violence against women are the most important factor getting married at the same age as young so they cannot control their emotions when there are problems, inadequate economic problems, infidelity, or a third person in a household, association wrong husband, emotional instability in the husband so that it often causes conflict. Then as for the impact that occurs on domestic violence, namely a deep sense of trauma to the victim, fear, the pain felt by the victim physically and psychologically, psychologically bad for the child and the last is separation or divorce which will result in securing the future of his wife and future child.